1993
DOI: 10.1084/jem.178.4.1139
|View full text |Cite
|
Sign up to set email alerts
|

Gene transcription in differentiating immature T cell receptor(neg) thymocytes resembles antigen-activated mature T cells.

Abstract: SummaryEarly in ontogeny thymocytes have a surface marker phenotype that resembles activated mature T cells but they lack expression of the T cell receptor (TCR) complex. We have made preparations of day 14/15 triple negative fetal thymocytes that exhibit the activated T lymphocyte markers CD25, intercdlular adhesion molecule 1, Ly-6A/E, CD44, and heat stable antigen and are rapidly proliferating as evidenced by flow cytometric examination of BrdU incorporation. We found that binding activities of the gene reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 46 publications
3
28
0
Order By: Relevance
“…Indeed, DN thymocytes from the adult thymus are able to produce IL-2 and other cytokines in response to a TcR-independent stimulation (36,68). However, as thymocytes reach the DP stage, they can no longer produce cytokines upon stimulation (9,11,48).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, DN thymocytes from the adult thymus are able to produce IL-2 and other cytokines in response to a TcR-independent stimulation (36,68). However, as thymocytes reach the DP stage, they can no longer produce cytokines upon stimulation (9,11,48).…”
Section: Discussionmentioning
confidence: 99%
“…The specific regulation of these transcription factors has been well studied during T-cell activation, but relatively little is known about the regulation during fetal (29,68) and adult (11,48,56) thymic development. Interestingly, Zúñiga-Pflücker et al showed that both AP-1 and NFAT are functional in DN thymocytes (68).…”
Section: Cd8mentioning
confidence: 99%
See 1 more Smart Citation
“…The POU family members Oct-1/Oct-2 were shown to interact specifically with a B cell-specific coactivator Bob 1 and this interaction was the main determinant for B cell-specific activation of Ig promoters [31]. It was also shown that expression of the Oct-2 gene is involved in T cell activation and thymocyte development [32][33][34]. In this study we detected differential interactions of Oct-1 and Oct-2 with CSB both in vivo and in vitro in the thymus.…”
Section: Discussionmentioning
confidence: 99%
“…NF-AT is transiently expressed in triple negative thymocytes and later in mature T cells following cell activation via the T cell receptor complex. The presence of an activated phenotype by these early T cell receptor negative thymocytes is attributed to an activation event likely mediated by a thymocyte-stromal cell interaction [119]. The early expression of NF-AT may be crucial for thymocyte development.…”
Section: Lymphoid Lineage Commitmentmentioning
confidence: 99%